2009
DOI: 10.1002/cbf.1623
|View full text |Cite
|
Sign up to set email alerts
|

Dose‐dependent actions of curcumin in experimentally induced myocardial necrosis: a biochemical, histopathological, and electron microscopic evidence

Abstract: Curcumin, an active component of turmeric, is a well-known antioxidant due to its reactive oxygen species (ROS) scavenging property. However, some in vitro studies have suggested that curcumin induces generation of ROS at higher doses and thus exerts pro-oxidant effect. We demonstrate, for the first time, the dose-dependent effects of curcumin in isoprenaline-induced model of myocardial necrosis in rats. The animals were assigned to control, isoprenaline and three curcumin treatment groups. Curcumin (100, 200,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 56 publications
(59 reference statements)
1
15
0
Order By: Relevance
“…In the present study curcumin was observed to alleviate the adverse effects of carbofuran on rat brain. Similar ameliorative effects of curcumin have been described by other workers (Tanwar et al, 2010). Though there are reports indicating the antioxidative and pro-oxidative properties of curcumin at lower and higher doses, respectively, the exact mechanism of interaction of curcumin with LDH is not known (Tanwar et al, 2010).…”
Section: Discussionsupporting
confidence: 90%
“…In the present study curcumin was observed to alleviate the adverse effects of carbofuran on rat brain. Similar ameliorative effects of curcumin have been described by other workers (Tanwar et al, 2010). Though there are reports indicating the antioxidative and pro-oxidative properties of curcumin at lower and higher doses, respectively, the exact mechanism of interaction of curcumin with LDH is not known (Tanwar et al, 2010).…”
Section: Discussionsupporting
confidence: 90%
“…The antioxidant action of curcumin resides in the inhibition of ROS production by repressing the catalytic subunits p67phox, p47phox and p22phox of nicotinamide adenine dinucleotide phosphate (NADPH) oxidase [52,53]. In parallel, curcumin reduces ROS by upregulating the expression of endogenous antioxidant enzymes, such as SOD, catalase, GSH-Px and HO-1 [54,55]. Another interesting mechanism by which curcumin exerts antioxidant effects is the preservation of the mitochondrial redox potential [13] that has been evidenced in vivo in rat hearts subjected to ischemia-reperfusion.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that the smaller dose was too small to generate a significant effect, especially since the low bioavailability of oral curcumin is well-known [18]. The larger dose (300 mg/kg bw) was also inefficient, possibly due to the pro-inflammatory effects of large doses of curcumin [19]; the 300 mg/kg bw dose administered in our study is approximately 1.7 grams when converted to human equivalent dose [20,21], which is significantly larger than the average doses used in clinical studies. The dose of 120 mg/kg bw induced a persistent antinociceptive effect in the Tail Flick test over a 3 hour period with a maximum effect at one hour.…”
Section: The Effect Of Curcumin On Experimental Painmentioning
confidence: 99%